Simultaneous Occurrence of Human Antibodies Directed against Fibrinogen, Thrombin, and Factor V Following Exposure to Bovine Thrombin: Effects on Blood Coagulation, Protein C Activation and Platelet Function - Chouhan, Vibhuti D; De La Cadena, Raul A; Nagaswami, Chandrasekaran; Weisel, John W; Kajani, Mehdi; Rao, A Koneti (Thrombosis and Haemostasis, 1997)
We describe a patient with severe epistaxis, prolonged coagulation tests and decreased plasma factor V following exposure to bovine topical thrombin. Patient IgG, but not normal IgG, showed binding to immobilized thrombin (bovine > human) and fibrinogen, and to factor V by Western blotting; the binding to thrombin was inhibited by hirudin fragment 54-65. Electron microscopy of rotary shadowed preparations showed complexes with IgG molecules attached near the ends of trinodular fibrinogen molecules. Patient IgG inhibited procoagulant, anticoagulant and cell-stimulating functions of thrombin demonstrated by inhibition of fibrinogen clotting, protein C activation and platelet aggregation; thrombin hydrolysis of S-2238 was not inhibited. The results suggest that the antibody is targeted against anion-binding exosite and not catalytic site of thrombin. Antifibrinogen antibodies have not been reported in patients exposed to bovine thrombin. There is a pressing need to re-evaluate the role of bovine thrombin as a therapeutic agent.